2015
DOI: 10.12720/ijsps.4.1.79-85
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Biceps Brachii Muscles in Dynamic Contraction Using sEMG Signals and Multifractal DMA Algorithm

Abstract: In this work, an attempt has been made to analyze surface electromyography (sEMG) signals in dynamic contraction using multifractal detrending moving average algorithm (MFDMA). The signals are recorded from biceps brachii muscles of twenty two healthy participants using a standard experimental protocol. The recorded sEMG signals are pre-processed and normalized by dividing the time axis into six equal segments. The first segment and sixth segment are considered as nonfatigue and fatigue conditions for analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 24 publications
1
16
1
Order By: Relevance
“…The signals are found to be highly complex in nonfatigue stage and there is a reduction in complexity during fatigue conditions. The result of reducing complexity in fatigue conditions concurs with previous work reported on biceps brachii muscles [25]. The 3-D visual plots are generated with DET, VMAX and complexity features for representing the nonfatigue and fatigue trends.…”
Section: Discussionsupporting
confidence: 83%
“…The signals are found to be highly complex in nonfatigue stage and there is a reduction in complexity during fatigue conditions. The result of reducing complexity in fatigue conditions concurs with previous work reported on biceps brachii muscles [25]. The 3-D visual plots are generated with DET, VMAX and complexity features for representing the nonfatigue and fatigue trends.…”
Section: Discussionsupporting
confidence: 83%
“…The values generalized Hurst exponent for nonfatigue and fatigue conditions are represented. H q in both nonfatigue and fatigue conditions exhibits decreasing trends with increasing order and this indicates multifractal characteristics of sEMG signal [9]. In the case of fatigue condition, H MAX increased and H MIN decreased indicating an increase of smaller fluctuations and reduction of large fluctuations respectively.…”
Section: Resultsmentioning
confidence: 88%
“…The multifractal technique is scale invariant analysis of time series [6]. Multifractal analysis of sEMG signals have been reported in previous studies using spectral features [7]- [9]. In this work, sEMG signals are analyzed using multifractal detrended moving average (MFDMA) algorithm with Hurst exponent features [10].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Ni et al, [68] showed that time, frequency, and time- Consequently, the aim of the present study was to determine the best MMF indicators, f rom 15 MMF indicators identified in the literature as potentially relevant to assess muscle fatigue during a repetitive pointing task (RPT) performed with the upper limb. We hypothesized that for the anterior and medial deltoids, which are the muscles showing the largest signs of fatigue during the upper limb repetitive task used in the present studies [72][73][74], the mobility, median frequency, spectral entropy, fuzzy entropy, multiscale entropy [24,28,41,75,76], and degree of multifractality [40,47,49,53] will have greater importance to predict the evolution of the RPE. In addition, these MMF indicators will significantly change for a large proportion of the participants in the anterior and medial deltoid in comparison to approximate and sample entropy, recurrence quantification analysis, correlation dimension, and the largest Lyapunov exponent [28,40,46,55].…”
Section: Introductionmentioning
confidence: 99%